Negotiating Sharia and Modern Finance: A Socio-Legal Study of Pesantren Practices in Conventional Banking in Banyumas Regency - Refani Andina Sari (Jurnal Syariah dan Hukum Komparatif, 2026)
Pesantren in Banyumas Regency actively negotiate the relationship between Sharia principles and modern financial systems through their engagement with conventional banking institutions. Using a qualitative socio-legal approach that integrates doctrinal analysis with field research in five pesantren, the study explores how Islamic legal reasoning—particularly concerning riba—is interpreted within institutional contexts. The findings reveal that most pesantren, especially those affiliated with Nahdlatul Ulama, adopt a pragmatic approach grounded in maslahah (public benefit), niyyah (intention), and tarāḍī (mutual consent), distinguishing between exploitative usury and administrative interest. Their use of conventional banks is justified as a necessity for financial security, efficiency, and compliance with state regulations. In contrast, a minority of Salafi-oriented institutions reject conventional banking entirely, emphasizing textual fidelity and moral purity. The study concludes that pesantren financial practices represent a form of applied ijtihād—a contextual reinterpretation of Islamic law balancing doctrinal integrity and institutional pragmatism. By situating pesantren as active agents within Indonesia’s plural legal and economic landscape, this research highlights how Sharia operates as a living, adaptive system guiding ethical engagement in contemporary finance.